Design and Implementation of Student Chat Bot using Machine Learning (International Journal of Innovative Research in Engineering & Management, 2022)
Students today are confronted with  numerous issues regarding college student information.In a college, there is no effective communication channel for  obtaining necessary student information.The automation  of web-based communication using computer  programming is the primary focus of this paper.A chat  bot, or conversational agent that responds to user  statements, is created using a computer program.It is able  to receive user input in a variety of formats, including  speech and text.The appropriate response to the user's  query is generated by combining LSA (Latent Semantic  Analysis) and AIML (Artificial Intelligence Markup  Language).The system will send an automatic ping to the  administrator if it cannot locate the appropriate response  to the user's query.
Keywords: AIML; LSA-based Artificial Intelligence Markup Language; :Analyses of Latent Semantics